Enfermos Terminales y Muerte Asistida: ¿Una Aproximación a los Derechos Humanos? - Arrobo García, David Ignacio (2018)
The content of this investigative text is originally explained as an attempt to assimilate the set of factors that intervene when premonitory ideas are installed in the individual diminished by the disease. Impossible to establish the accuracy of the place they will ever occupy in thought, and in the space of family and friends, each section described here is susceptible to addition. To be able to understand the approach of medically assisted death, it is necessary, as is done in the conceptual development, to analyze human death, the reaction of the person who is about to die, the one who is suffering from a serious illness that has caused pain and suffering intolerable. As the investigation progresses, the position that medicine has occupied, and the doctor, specifically, in the societies of the world, begins to be seen; how bioethics has been established simultaneously with medical technology in constant innovation, to face the therapeutic fury, stubborn action of obstinate doctors. The prevalence of human rights, universally recognized as the ideal of nations, provides the essential contribution to the argument of the present. I have made a brief account of its historical significance, because, without doubt, the availability that a man has in the stages of life, becoming more visible with comes of age and the maturity that it entails, is closely linked to 5 the freedom, habitually named not only in the legal field, but, of obligatory protection of the State towards the inhabitants. The legal proposal for legal reform, decisive for what was announced, supported by international legislation ratified by and in the Ecuadorian Constitution, reveals the human reaction to suffering, and the response in law to address it comprehensively.